Lead-Free Piezoelectrics 2011
DOI: 10.1007/978-1-4419-9598-8_5
|View full text |Cite
|
Sign up to set email alerts
|

Lead-Free KNN-Based Piezoelectric Materials

Abstract: Sodium potassium niobate with the general chemical formula of K 1 À x Na x NbO 3 (KNN hereafter) is one of the most attractive lead-free materials which have been extensively investigated throughout the last decade.KNN is a solid solution of NaNbO 3 (NN) and KNbO 3 (KN) compounds. A KNN phase diagram comprised of the tetragonal, orthorhombic, and monoclinic ferroelectric regions and an orthorhombic antiferroelectric region is depicted in Fig. 5.1.The phase transitions and variations of dielectric properties of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 125 publications
(163 reference statements)
0
12
0
Order By: Relevance
“…However, the environmental and human health concerns due to the toxicity of lead forced the researchers to look for non-hazardous alternatives [1]. The most widely studied lead-free piezoceramics are based on the perovskite systems K 0.5 Na 0.5 NbO 3 (KNN) [2], (Na 1/2 Bi 1/2 )TiO 3 (NBT), BiFeO 3 [3], and (Ba,Ca)(Zr,Ti)O 3 (BCZT) [4,5]. The solid solution of Ba(Zr 0.2 Ti 0.8 )O 3 -(Ba 0.7 Ca 0.3 )TiO 3 was presented by Liu and Ren [6] as a pseudobinary ferroelectric system with a morphotropic phase boundary (MPB) and exceptionally-high electromechanical properties.…”
Section: Introductionmentioning
confidence: 99%
“…However, the environmental and human health concerns due to the toxicity of lead forced the researchers to look for non-hazardous alternatives [1]. The most widely studied lead-free piezoceramics are based on the perovskite systems K 0.5 Na 0.5 NbO 3 (KNN) [2], (Na 1/2 Bi 1/2 )TiO 3 (NBT), BiFeO 3 [3], and (Ba,Ca)(Zr,Ti)O 3 (BCZT) [4,5]. The solid solution of Ba(Zr 0.2 Ti 0.8 )O 3 -(Ba 0.7 Ca 0.3 )TiO 3 was presented by Liu and Ren [6] as a pseudobinary ferroelectric system with a morphotropic phase boundary (MPB) and exceptionally-high electromechanical properties.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that the functional properties of KNN solid solution were affected by the Na/K ratio, with MPB being formed by two adjacent orthorhombic ferroelectric phases, however, the properties are not markedly improved at MPB region [278]. One of the main obstacles in the development of KNN-based ceramics is the difficulty to achieve dense ceramics because of the evaporation of the alkali components at high temperature.…”
Section: Loss Behavior Of Selected Ferroelectricsmentioning
confidence: 99%
“…The sample sintered by the conventional method has greater permittivity without dispersion, while the values of the dielectric constant of the samples sintered by microwaves have very low permittivity values at frequencies from 0 to 10 MHz. The porosity observed in the microstructure of the microwave-sintered piezoelectric materials affects the density of the material, and these defects cause a decrease in the dielectric values [37,38].…”
Section: Sintering Of K05na05nbo3 Powdersmentioning
confidence: 99%